Evaluasi Kecernaan Bahan Kering, Bahan Organik dan Protein Kasar Tongkol Jagung Fermentasi dengan Penambahan Sumber Karbohidrat yang Berbeda secara In vitro - T. Astuti; S. A. Akbar; A. P. Putri (Jurnal Peternakan, 2020)
This research aimed to evaluation the affect of corn cob fermented with Phanerochaete chrysosporium by adding the different sources of carbohydrates on the digestibility of dry matter, organic matter, and crude protein by in-vitro methods. The treatments were : P0 = fermented corn cobs without carbohydrate, P1 = fermented corn cobs + 10% rice bran; P2 = fermented corn cobs + 10% tapioca flour; P3 = corn cob fermented + 10% molasses, and using a compleately randomize design for varian analize. The resulted of this study shown a very significant affected (P <0.01) on the digestibility of dry matter and organic matter but no affected (P> 0.05) on crude protein digestibility. The best results digestibility of dry matter (66.98%) on the P3 treatment adding molasses, and the highest digestibility of organic matter (67.49%) on the P3 treatment too, but the highest digestibility of crude protein (51.37%) in P1 treatment (adding by rice bran).